Beliefs affecting ART adherence in newly diagnosed HIV-positive participants in Manzini, Eswatini - Thabiso Mango; Mambwe Kasese-Hara; Mamakiri Mulaudzi (AOSIS, 2024)
Background: Achieving optimal adherence to antiretroviral therapy (ART) is challenging. Consistency in HIV care and treatment is crucial for achieving viral load suppression and preventing HIV-related illnesses, disease progression to AIDS, mortality, drug resistance, and onward transmission. Objectives: The purpose of this research was to gain a comprehensive understanding of the beliefs that play a role in determining the level of ART adherence among individuals newly diagnosed with HIV. By examining these beliefs, the researchers aimed to identify potential barriers and facilitators to adherence, ultimately contributing to the development of effective interventions and strategies to improve ART adherence. Method: An exploratory qualitative approach was employed in this study, utilising the Theory of Planned Behaviour (TPB) as its theoretical framework. To gather insights, in-depth interviews were conducted with 19 participants recruited post diagnosis, who shared their beliefs regarding ART adherence. Thematic analysis identified beliefs, categorised under TPB precursors, namely behavioural outcomes, subjective norms, and perceived behavioural control. Results: Participants emphasised health improvement, treatment effectiveness, and disease prevention as advantages to ART adherence, while disadvantages included fear of lifelong commitment, side effects, and stigma. ART adherence was enhanced by family support but impeded by a number of social factors. Participants expressed confidence in creating personal reminders or seeking external help, but anticipated various challenges. Conclusion: The research has shown that the beliefs affecting ART adherence in individuals recently diagnosed with HIV but not yet on treatment are like those that have been reported to influence adherence in HIV-positive participants currently receiving treatment.